English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-11-27 06:06:29 · 15 answers · asked by Anonymous in Science & Mathematics Mathematics

15 answers

The goal here is to find the equation with x on one side and everything else on the other. It's like the equation you have, but instead of y= you want x=. So you need to "solve for x." Think of y as just a number, and you need to find what x =.

Step by step:

y=4x+4

Subtract 4 from each side:

y-4=4x

Divide both sides by 4

(y-4)/4=x

x=(y-4)/4

There's your equation! Hope this helps.

2006-11-27 06:07:29 · answer #1 · answered by Aegor R 4 · 2 1

There's confusion here about what an equation is and what a function is. The above equation establishes that y IS a function of x, namely:

y = f(x) = 4x + 4 (1).

The insertion of f(x) into this eqn. simply defines the needed function.

The "answers" so far given are in fact rewriting eqn. (1) so that x is given AS A FUNCTION OF y, namely:

x = g(y) = (y - 4)/4 (2).

Eqn. (2) defines g(y), the function needed to express x as a function of y. This is something quite different from what the question asks for. (A "function of x" has to show the dependence of f on its argument x, not some other variable.)

Live long and prosper.

2006-11-27 06:22:19 · answer #2 · answered by Dr Spock 6 · 1 0

x = ¼y - 1

2006-11-27 06:08:35 · answer #3 · answered by Dave 6 · 1 1

Subtract 4 from both sides:
4x=y-4

Divide 4 on both sides:
x=1/4y-1

2006-11-27 07:15:14 · answer #4 · answered by Anonymous · 0 0

x = a million/2y - 3/2 this equation is authentic i promise!!! illrun you by it. 4x - 2y = -6 first upload 2y to the two factors!!! then u have, 4x = 2y - 6 then you definitely could divide the two factors by 4 so as which you will get x on my own. now u have x = 2/4y - 6/4 yet you're able to simplify.

2016-10-04 10:35:25 · answer #5 · answered by ? 4 · 0 0

y = 4x + 4
subtract 4 from both sides
y - 4 = 4x
divide both sides by 4
(y-4)/4 = x
or
x = y/4 -1

2006-11-27 06:09:18 · answer #6 · answered by tj70555 2 · 1 1

y = 4x + 4

- 4x + y = 4x + 4 - 4x

- 4x + y = 4

- 4x + y - 4 = 4 - 4

- 4x + y - 4 = 0

- 4x + y - 4 - y = 0 - y

- 4x - 4 = - y

- 4x - 4 + 4 = - y + 4

- 4x = - y + 4

- 4x/-4 = - y/-4 + 4/- 4

x = y/4 + (- 1)

x = 1/4y - 1

The answer is x = 1/4y - 1

- - - - - - s-

2006-11-27 07:05:18 · answer #7 · answered by SAMUEL D 7 · 1 0

y=4x+4

=>y-4=4x

=> x= (y-4)/4

2006-11-27 06:16:17 · answer #8 · answered by §wëet @ heãrt 2 · 1 0

y = 4x + 4 subtrac 4 from each side
4x=y-4 divide by 4
x=y/4-1

2006-11-27 06:12:14 · answer #9 · answered by yupchagee 7 · 1 1

It is already a function of X, where y = f(x) = 4(x+1). Does it satisfy you?

2006-11-27 06:15:41 · answer #10 · answered by golgolbaat 3 · 1 0

fedest.com, questions and answers